2009
DOI: 10.1017/s1742058x09090031
|View full text |Cite
|
Sign up to set email alerts
|

ABLACKMAN IN THEWHITEHOUSE?

Abstract: Race and patriotism were recurring themes during the 2008 presidential campaign that were used to highlight differences between Barack Obama and his opponents. Yet we know little about how racism and patriotism ultimately affected support for Obama among Whites. Appeals to working-class Whites, a lot of which were thinly veiled allusions to Obama's race and perceived lack of patriotism, also figured prominently in the campaign. Accordingly, this paper explores how racism and patriotism shaped support for Obama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Research on the Obama candidacy 2 offers insights for addressing all three questions. These studies explore the electoral implications of attitudinal constructs like campaign image (Block and Onwunli, 2010; Kenksi, Hardy, and Hall‐Jamieson, 2010; Fiske et al, 2009), voter personality (Jost, West, and Gosling, 2009), implicit cues (Berenski et al, 2009; Pasek et al, 2009; Payne et al, 2009), group‐based considerations (Harris‐Lacewell and Junn, 2007; Ramakrishnan et al, 2009; Roane, 2009), stereotypes (Ford, Maxwell, and Shields, 2010; Parker, Sawyer, and Towler, 2009; Segura and Valenzuela, 2010), experiences with discrimination (Hunt and Wilson, 2009), emotions toward Blacks (Dwyer et al, 2009), perceived threat (Eibach and Prudie‐Vaughns, 2009; Liu, 2010; Lugo‐Lugo and Bloodsworth‐Lugo, 2009), media messaging (Kenksi, Hardy, and Hall‐Jamieson, 2010), party loyalties (Wallace et al, 2009), and policy preferences (Hutchings, 2009). A complete review of this growing literature is beyond the scope of the current article; my goal is to speak more generally about the importance of racial attitudes to the Obama vote, and doing so requires that I organize racial attitudes by broader themes.…”
Section: Racial Attitudes and The Obama Votementioning
confidence: 99%
See 1 more Smart Citation
“…Research on the Obama candidacy 2 offers insights for addressing all three questions. These studies explore the electoral implications of attitudinal constructs like campaign image (Block and Onwunli, 2010; Kenksi, Hardy, and Hall‐Jamieson, 2010; Fiske et al, 2009), voter personality (Jost, West, and Gosling, 2009), implicit cues (Berenski et al, 2009; Pasek et al, 2009; Payne et al, 2009), group‐based considerations (Harris‐Lacewell and Junn, 2007; Ramakrishnan et al, 2009; Roane, 2009), stereotypes (Ford, Maxwell, and Shields, 2010; Parker, Sawyer, and Towler, 2009; Segura and Valenzuela, 2010), experiences with discrimination (Hunt and Wilson, 2009), emotions toward Blacks (Dwyer et al, 2009), perceived threat (Eibach and Prudie‐Vaughns, 2009; Liu, 2010; Lugo‐Lugo and Bloodsworth‐Lugo, 2009), media messaging (Kenksi, Hardy, and Hall‐Jamieson, 2010), party loyalties (Wallace et al, 2009), and policy preferences (Hutchings, 2009). A complete review of this growing literature is beyond the scope of the current article; my goal is to speak more generally about the importance of racial attitudes to the Obama vote, and doing so requires that I organize racial attitudes by broader themes.…”
Section: Racial Attitudes and The Obama Votementioning
confidence: 99%
“…Pessimistic Whites—that is, those who believe that race relations remain wanting—are significantly more favorable about an Obama presidency. Optimistic Whites (the ones who perceive little discrimination) tend to think less positively about the prospect, pardon the cliché, of a “Black man in the White House” (Parker, Sawyer, and Towler, 2009). Hunt and Wilson's findings describe the “direction” of the relationship between attitudes about race relations and vote choice.…”
Section: Racial Attitudes and The Obama Votementioning
confidence: 99%
“…This phenomenon can be conceptualized as a form of exclusionary patriotism (Sidanius & Petrocik, ): National attachment becomes inextricably linked to a relative exclusion of subgroups that do not embody the dominant definition of the national identity. In line with this idea, survey data showed that the more White respondents, particularly those in the working class, expressed an attachment to U.S. symbols, the less likely they were to vote for Obama (Parker, Sawyer, & Towler, ). Similarly, a longitudinal study revealed antiegalitarian voters opposed Obama due to his perceived foreignness (Knowles, Lowery, & Schaumberg, ).…”
mentioning
confidence: 95%
“…Brent Staples, for example assumes the nuance of Obama"s speeches reflect the subtleties of a man who consciously refuses crass racial politics but instead bespeaks an ideal that transcends racial particularism (2009a; 2009b). Others such as Parker et al, (2009) readily assume racism was a ploy used by Hilary Clinton and John McCain, and it was, but not deployed by Barack Obama. The rejection of my thesis is implied in the work of Galen and Bodenhausen (2009;See also Ford, 2009;Eibach and Purdie-Vaughns, 2009).…”
Section: Race and The Votementioning
confidence: 99%